Economic sociology – old and new. (1st January 2011) - Daoud, Adel; Larsson, Bengt
In this article, we discuss 'classical' sociology and 'new' economic sociology to show the interest of sociologists in economic issues and to examine the relationship between economics and sociology from a sociological perspective. We maintain that, besides empirical studies, sociologists have contributed to the analysis of economic systems, organisations, and action through the development of theoretical approaches to answer two basic questions: Why are the neoclassical assumptions about action problematic? And how are rational economic actions and systems produced? Sociologists have worked on three frontiers to answer these questions. First, by developing a more nuanced action theory. Second, by elaborating the concept of embeddedness to capture how economic action is influenced by cognitive, cultural, structural, and political contexts. Third, by understanding the historical differentiation and rationalisation of institutions and action contexts that produces instrumental rationality.